The Artistry of Innovation: Increasing Teachers’ Artistic Quotient for Innovative Efficacy - Martin, Brittany Harker (Canadian Journal of Education/Revue canadienne de l’éducation, 2019)
This article presents a new model of building capacity for innovative teaching that I call Artistic Quotient (AQ). The purpose of the study was to test the model with generalist teachers who were registered in a professional learning program for innovative teaching through the arts. The procedure employed a one-way, within-subjects, quasi-experimental design using psychometric scales to measure program effects through pre- and post-surveys. Results include a statistically significant increase in teachers’ creative and aesthetic capabilities and innovative teacher efficacy, with the conclusion that increasing teacher AQ increases innovative teacher efficacy. Implications for teacher preparation, professional learning, and innovation education are discussed. Keywords: Artistic Teacher; Artistic Quotient (AQ); Teacher Innovation; Arts Integration; Creative Practice; Design Thinking; Aesthetic Awareness; Innovative Teacher Efficacy; Artistic Capabilities; Social Learning Theory